Numerical simulation of slider air bearings in head-disk interface system based on a mesh-free method - Li, Xu Hong (2008)
In this thesis, a mesh-free methodology is developed for modeling and simulating air bearing sliders in hard disk drives. The developed CMMS Air Bearing Design Program implements mesh-free method to simulate complex air bearing sliders with shaped rails, multiple etch depths and highly recessed regions.